2022
DOI: 10.1177/23743735211069825
|View full text |Cite
|
Sign up to set email alerts
|

Rural Patients’ Perceptions of Their Potentially Preventable Hospitalisation: A Qualitative Study

Abstract: Potentially preventable hospitalisations (PPHs) occur when patients receive hospital care for a condition that could have been more appropriately managed in the primary healthcare setting. It is anticipated that the causes of PPHs in rural populations may differ from those in urban populations; however, this is understudied. Semi-structured interviews with 10 rural Australian patients enabled them to describe their recent PPH experience. Reflexive thematic analysis was used to identify the common factors that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 60 publications
(68 reference statements)
0
20
0
Order By: Relevance
“…A further 26 papers were excluded for not meeting inclusion criteria, leaving 13 papers for review and analysis ( Figure 1 ). Eight papers were quantitative/descriptive studies [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] and five were qualitative studies [ 40 , 41 , 42 , 43 , 44 ]. Only one study reported no statistically significant association between the variables studied (physician supply) and rural PPH risk [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A further 26 papers were excluded for not meeting inclusion criteria, leaving 13 papers for review and analysis ( Figure 1 ). Eight papers were quantitative/descriptive studies [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] and five were qualitative studies [ 40 , 41 , 42 , 43 , 44 ]. Only one study reported no statistically significant association between the variables studied (physician supply) and rural PPH risk [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The population for study was variably described; this included being conducted in administrative areas serviced by “rural Indian Health Services” [ 34 ] or rural “health professional shortage areas” in Nebraska [ 39 ]. Other studies described a specific rural region of Tasmania [ 36 , 40 , 41 ], Victoria [ 32 ], or New South Wales [ 37 , 42 , 43 , 44 ] as the setting. The remainder used large, usually national, datasets from which rural patient data could be extracted.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent Australian study sought to identify common risk factors that rural patients described as contributing factors associated with their recent PPH. 2 They found that health literacy, social support networks, the ability to access primary healthcare services, and perceptions of primary care were determinants of PPH risk. While access and utilisation of wellintegrated primary healthcare services is a part of the solution, the researchers emphasise that community- and individuallevel factors also need to be addressed when considering future interventions.…”
Section: Preventablementioning
confidence: 99%